Analysis of the relationship between GLUT family in the progression and immune infiltration of head and neck squamous carcinoma - Li, Bing (Diagnostic pathology, 2023)
Head and neck squamous cell carcinoma (HNSCC) causes much health and economic burden, and the therapeutic results must be improved. Glucose metabolism is an essential component of tumor metabolism and is instrumental in its development. Glucose transporter types (GLUTs) can uptake glucose from the extracellular matrix (ECM), regulating cellular metabolism in several cancers. However, the function of different GLUT proteins in HNSCC remains unclear. To clarify the role of GLUTs in HNSCC, several open-access online databases (Oncomine, GEPIA, Kaplan–Meier, cBioPortal, GeneMANIA, and TIMER) were used to evaluate the differential expression, clinical significance, genetic alteration, and relative immune cell infiltration. The expression of GLUTs was detected in clinical patient samples by immunohistochemistry. The mRNA level of SLC2A1/3 significantly increased in HNSCC, while SLC2A4 reduced. SLC2A3 was related to the advanced clinical stage and short overall survival (OS) in HNSCC. Also, higher SLC2A1/2 mRNA expression was related to shorter OS in HNSCC patients. The expression of GLUTs was related to diverse immune cells, including B cells, CD4 + T cells, CD8 + T cells, dendritic cells (DCs), macrophages, and Treg cells in HNSCC. Moreover, the high expression of GLUTs was demonstrated by immunohistochemistry in patient tissues. GLUTs might have a potential role in HNSCC's progression and development. Therefore, the current findings might offer a novel perception for selecting GLUT family prognostic markers and treatment for HNSCC patients.